Political connections and debt restructurings - Halford, Joseph T.; Li, Chengcheng (Journal of Corporate Finance, 2020)
This paper presents evidence that distressed firms with politically connected executives and board members are more likely to reorganize outside of court than to file for Chapter 11 bankruptcy. This relation is more evident for firms that have more political importance, such as major employers within a state, firms located in swing states, and in periods leading up to major election dates. The evidence suggests that the expected costs of financial distress are lower for politically connected firms which may partially explain the higher leverage ratios of politically connected firms documented in the extant literature.